2008
DOI: 10.1002/ps.1689
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of emamectin benzoate to Cydia pomonella (L.) and Cydia molesta (Busck) (Lepidoptera: Tortricidae): laboratory and field tests

Abstract: Emamectin benzoate may be considered a valuable tool for the control of codling moth as a component of an IPM programme. Its collective advantages are: high efficacy, lack of cross-resistance with currently used products, control of secondary pests such as oriental fruit moth and selective toxicity that spares beneficials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
(23 reference statements)
1
25
1
Order By: Relevance
“…The current study therefore supports the notion that aqueous plant extracts are relatively harmless to natural enemies [49][50][51] and can be integrated with biological pest control unlike synthetic insecticides such as Attack which has deleterious effects on natural enemies. This insecticide (Attack) is a semi-synthetic derivative of the natural product abamectin in the avermectin family 52,53 . It is considered to have minimal effect on predators and parasitoid because it degrades rapidly through sunlight on the leaf surface resulting in shorter contact periods in the crop environment 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study therefore supports the notion that aqueous plant extracts are relatively harmless to natural enemies [49][50][51] and can be integrated with biological pest control unlike synthetic insecticides such as Attack which has deleterious effects on natural enemies. This insecticide (Attack) is a semi-synthetic derivative of the natural product abamectin in the avermectin family 52,53 . It is considered to have minimal effect on predators and parasitoid because it degrades rapidly through sunlight on the leaf surface resulting in shorter contact periods in the crop environment 52 .…”
Section: Discussionmentioning
confidence: 99%
“…This insecticide (Attack) is a semi-synthetic derivative of the natural product abamectin in the avermectin family 52,53 . It is considered to have minimal effect on predators and parasitoid because it degrades rapidly through sunlight on the leaf surface resulting in shorter contact periods in the crop environment 52 . Some studies have found Attack ® less harmful to natural enemies than other synthetic insecticides and therefore recommend its inclusion in integrated pest management programmes e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The codling moth, Cydia pomonella (L.) (Lepidoptera, Tortricidae), is an economically important pest on pome fruit worldwide. Control of codling moth largely relies on insecticides [20], although mating disruption has been developed as an environmentally safe alternative [21], [22]. In mating disruption, sexual communication and mate-finding is disrupted by aerial permeation of apple orchards with synthetic pheromone.…”
Section: Introductionmentioning
confidence: 99%
“…(Yen &Lin 2004 andAndersch et al 2011). Emamectin benzoate is a novel macrocyclic lactone insecticide derived from naturally occurring avermectin molecules isolated by fermentation from the soil microorganism Streptomyces avermitilis (Ioriatti et al 2009).…”
Section: Introductionmentioning
confidence: 99%